Reversal of restraint stress caused dendritic atropy in rats by Nardostachys jatamansi - Gloria Karkada
Hippocampus and prefrontal cortex of brain have distinct role in encoding and retrieval of memories. Uncontrollable stress may influence the structural alterations of limbic brain regions and atropy of neurons mainly in the regions like the prefrontal cortex and hippocampus. Nardostachys jatamansi (D. Don) DC (NJE) is a perennial herb and is known for its anti-Parkinson$1 (Bs, hepatoprotective, neuroprotective, hypotensive and anti-diabetic activities. Even though, it is an effective therapeutic intervention for memory impairment but, its effect on the neurons of the hippocampus is not clear. In this context, the effect of NJE on chronic restraint stress induced dendritic atropy in rats was studied. Male Wistar rats underwent 21 days of restraint stress in a close fitting rodent restrainer. In combined treatment groups rats were treated with alcoholic extract of NJE at dosage of 200 mg/kg bw for 21 days along with chronic restraint stress. The dendritic morphology of neurons was studied in Golgi-impregnated sections. Stress produced dendritic atropy significantly increased the dendritic branching and intersections in experimental rats. Interestingly, treatment of stressed rats with NJE extract resulted in the reversal of stress induced the dendritic atrophy. These results demonstrate that atrophy of dendritic neurons caused by chronic restraint stress may be responsible for learning and memory impairment. Co-treatment of rats with NJE showed enhancement in the dendritic branching in the hippocampus. Furthermore, NJE treatment significantly increased superoxide dismutase activity and total antioxidant capacity in frontal cortex, hippocampus and striatum regions of brain. Thus, our findings suggest that NJE is a potential neuroprotector, which might be beneficial in the treatment of stress induced memory impairments